Character improvement based on digital literacy through internalization of Tamansiswa Tri-Nga teachings in class V elementary school students - Wulandari, Dika; Khosiyono, Banun Havifah Cahyo; Sulaimon, Jamiu Temitope (Tuladha : Jurnal Pendidikan Dasar, 2024)
Character is an important aspect that needs to be developed at this time, considering that various challenges and obstacles that come from outside are very dangerous for the character condition of Indonesian children. The aim of this research is to determine students' perceptions and implementation regarding the importance of character in strengthening digital literacy-based character education through internalizing the teachings of Tamansiswa Tri-Nga. Character education must be carried out well and continuously. The strengthening of character education carried out at SDN Klumpit through digital literacy-based character education through the internalization of Tri-Nga Tamansiswa teachings has gone well but needs to be carried out continuously so that students not only understand, but also have to achieve. action so that the value of love for one's country can be embedded among students.